CHEMICAL PROFILING OF SUTHERLANDIA FRUTESCENS AND S. MICROPHYLLA - Mncwangi, N.; Viljoen, A.; Manley, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Sutherlandia frutescens and its taxonomic ally, S. microphylla are indigenous to southern Africa and both boast an impressive history as an ethnomedicinal plant. The uses are diverse, spanning from the use against infectious diseases to the use against wasting to the treatment of diabetes and inflammation. More recently S. frutescens has been used in the treatment of conditions associated with HIV. The various pharmacological properties are ascribed to the presence of amino acids, triterpenes and glycosides. Despite the extensive use, published scientific studies focusing on the phytochemical profile and variations are scarce. This is crucial in unravelling the scientific rationale for the past and present day uses and possibly provides valuable information to optimise harvesting protocols and could contribute to good manufacturing practices. The aerial parts of S. frutescens (n=125) and S. microphylla (n=20) were collected from natural and cultivated sites. Near infrared spectroscopy (NIRS) was used to determine to potential of this technique to distinguish between the two species. The amino acids and pinitol were quantified with high performance liquid chromatography (HPLC). High-pressure thin layer chromatography (HP-TLC) was used to assess the consistency in the chemical fingerprint for the various samples. NIRS shows no difference between the two species. This technique was however not sensitive enough to quantify the amino acid content through NIRS calibration. The quantitative variation of amino acids and pinitol within and between natural populations and individual plants in a cultivation site was noted and these results will be discussed.